Transient Neonatal Diabetes Associated with Chromosome 6Q24 Imprinting Abnormalities Part 4. Differential Diagnosis and Treatment - O.Ye. Abaturov; A.O. Nikulina; O.O. Rusakova; I.O. Hirina; N.M. Lybenko (Zaslavsky O.Yu., 2016)
The article presents the differential diagnosis of diseases that occur with neonatal hyperglycemia. The common causes of neonatal hypoglycemia, variants of its combination with clinical manifestations from the various organs and systems are indicated. There was presented an algorithm for the choice of therapeutic measures in transient neonatal diabetes mellitus (TNDM). The features of diet in newborns, insulin therapy and other directions of drug treatment were described. There was provided the information about medical funds of this syndrome, which can be used in the organization of the diagnosis and treatment in children with 6q24-TNDM.